Prevalence and intensity of parasite on marine fishes at Bintuka river, Beaufort, Sabah / Mohamad Syahfiq Osman - Osman, Mohamad Syahfiq (2017)
Bintuka River, Beaufort is the fishing site for the fisherman around the villagers which located at the western part of Sabah, Malaysia. The research conducted to determine the parasites on fishes, determine the prevalence rate and intensity of parasites and to compare the infestation of parasites in different fish species. The fish caught using the fishing rod technique at three different station along the Bintuka River. Scrapping-technique been applied to get the ectoparasite on the fish and the intestine was taken by dissecting the fish stomach for the detection of endoparasite. Detection of parasite has been done at laboratory by using the compound microscope. The prevalence and intensity was calculated by using IBM SPSS Statistic ver.23 statistical analysis one-way ANOVA for the comparison of infestation parasites in different marine fish. There were 41 marine fishes caught during the research and total of 314 parasite were detected. The type of dominant parasites determined were under phylum Arthropoda which is Agauides sp. The prevalence rate of parasite is 95.32% and the intensity rate is 7.7 .There was no statistically significant difference (P > 0.05) in total parasite based on the fish species that have been caught. Lutjanus johnii fish species have the high infestation of parasites among the marine fish species at Bintuka River, Beaufort with the total parasite of 94. High rate infestation of parasite may become the potential cause of fish mortality. This finding has important implications for ecology and aquaculture at the study site.